The Role Of Satisfaction And Commitment As Mediators Of Service Quality And Perceived Risk On The Loyalty Of Tourists Staying At Former Covid-19 Isolation Patient Hotels In Bali - I Wayan Suardana; Putu Saroyini Piartrini; Ni Made Ariani; I Putu Gede Andika Putra Mahayana (CV. AFDIFAL MAJU BERKAH, 2023)
Tourist loyalty is widely regarded as a crucial driving force for the success of businesses in the tourism industry, including destination marketing. Tourists' choice of accommodation is greatly influenced by the attitudes or perceptions they acquire, which in turn determines their commitment to returning to the same hotel. The fundamental aim of this research is to explore how satisfaction and commitment mediate the development of tourist loyalty towards hotels in the post-COVID-19 era. The research employs a quantitative approach and entails conducting a survey among 225 foreign tourists accommodated in post-COVID-19 quarantine hotels. All data are analyzed using SEM PLS analysis. The findings of the study reveal that service quality and risk perception exert a positive and statistically significant influence on the satisfaction levels of tourists residing in post-COVID hotels. The better the service quality and the lower the travel risk perception, the stronger the satisfaction and commitment of tourists to these quarantine hotels. Satisfaction acts as a mediator in the relationship between service and commitment. Commitment is proven to mediate the relationship between service quality and tourist loyalty. Tourist loyalty to a product is not solely determined by low risk; rather, if tourists have positive perceptions, commitment performance will increase. Therefore, satisfaction acts as a precedent to commitment and tourist loyalty. Health risks can be minimized by continuing to implement health regulations in hotels, thereby enhancing tourist trust..